Detection of natural inter- and intra-genotype recombination events revealed by cap gene analysis and decreasing prevalence of PCV2 in wild boars - Cadar, Daniel; Cságola, Attila; Lőrincz, Márta; Tombácz, Kata; Spînu, Marina; Tuboly, Tamás (Infection, genetics and evolution, 2012)
► Genetic diversity of PCV2 in wild boars was studied. ► We detected that intra- and inter-genotype recombinations in wild boars are diverse. ► The recombination events may contribute to the genetic diversity of PCV2. ► These recombinations may also be the source of emergence of new PCV2 strains. Porcine circovirus type 2 (PCV2), the causative agent of a number of PCVAD (porcine circovirus associated diseases), is ubiquitous in domestic pig and wild boar populations. In the present study, using recombination detection program, phylogenetic analysis and base-by-base comparison of 28 PCV2 ORF2s (capsid protein coding gene) from wild boars and 8 from domestic pigs of Transylvania, recent natural intra- (PCV2b-1B/PCV2b-1C) and inter-genotype (PCV2a-2D/PCV2b-1C) recombination events were detected. Notably, one potential recombinant (F1-21) was detected in domestic pig with possible parental strains of wild boar origin. The estimated recombinant breakpoints comprised epitopes A, B and C of ORF2, without major changes in amino acid sequences. The prevalence of PCV2 in the wild boar population during the 5-year period following the first outbreaks of postweaning multisystemic wasting syndrome (PMWS) in domestic pigs in Romania showed a decrease from 13.4% to 8.3%. To our knowledge, this is the first study to show the existence of ORF2-based intra- and inter-genotype recombination in wild boar populations and the possible recombination between PCV2 strains of wild boars and domestic pigs. Our results suggest a certain independence of PCV2 infection in wild boar populations and demonstrate the possibility of infection with multiple PCV2 genotypes under natural circumstances. On the other hand, PCV2 genotypes specific for wild boars could be detected in domestic pig at lower frequency suggesting the possible spread of wild boar PCV2 to domestic swine. The recombination events described here may contribute to the genetic diversity of PCV2 and may also be the source of emergence of new PCV2 strains.